Pendampingan Sertifikasi Halal Mandiri (Self Declare) pada UMKM Kabupaten Mandailing Natal - Z Hrp, Ade Khadijatul; Fitri, Sari; Batubara, Yenni (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
To guarantee the halalness of a product that is produced, MSMEs need halal certification. Not only is it a guarantee of halal products, but this halal certificate is also something that MSMEs must have to improve the quality of their competitiveness. However, currently there are still many MSMEs that do not have halal certificates, especially in Mandailing Natal Regency. Because this service was carried out in Mandailing Natal Regency, it was carried out with partners, namely the Mandailing Natal Regency Cooperatives and SMEs Service, MUI Mandailing Natal Regency, Ministry of Religion Mandailing Natal Regency and PPH. Meanwhile, there are 25 MSMEs assisted by micro and small business actors who do not yet have a halal certificate with an implementation time of 30 days (1 month), namely in October 2025. The implementation of this service is carried out by providing outreach to SMEs about independent halal certification (self declare) in the form of an FGD, then providing halal certification registration assistance to SMEs who are accompanied by partners. The results of this service show that it is important to provide understanding or education to SMEs about halal guarantees for the products they produce, because there are still many SMEs who still experience limitations in developing NIBs, limitations in mastering and processing technology in using halal product guarantee system applications/websites (halal), so SMEs need intensive assistance.